Rare Case of Transcutaneous Oxygen Desaturation in a Cancer Patient: A Case Report and Diagnostic Approach for a Recurrent Problem. Issue 4 (15th February 2019) - Bachmann, Kaspar F.; Nebiker, Mathias; Johner, Caroline; Bregy, Rachel; Schaller, André; Novak, Urban; Jakob, Stephan M.
Abstract : We present a case of a 73-year-old cancer patient with low transcutaneous oxygen saturation who was transferred to the intensive care unit after deployment of the rapid response team. Differential diagnosis remained broad until methemoglobinemia (MetHb) was detected. MetHb was induced by administration of rasburicase, which was given to prevent tumor lysis syndrome. In a follow-up examination, glucose-6-phosphate dehydrogenase deficiency was found to be the cause of MetHb after rasburicase exposure. Diagnosis was made by either measuring arterial MetHb or CO oximeter. Treatment options involve transfusion and methylene blue, if glucose-6-phosphate dehydrogenase deficiency is not present. Abstract : Supplemental Digital Content is available in the text.